PROFILE OF ELDERLY PEOPLE WHO NEEDED DENTURE AT WAJO REGENCY: PROFIL MASYARAKAT LANJUT USIA YANG MEMBUTUHKAN GIGI TIRUAN DI KABUPATEN WAJO - Edy Machmud (Dentika: Dental Journal, 2010)
The main problem faced by the elderly people is tooth loss. A number of tooth loss will affect a health in general, as it will disrupt mastication process and finally will cause malnutrition and gastritis. Therefore, teeth should be substituted with dentures. The aim of this study was to have a picture of elderly people profile who needed a denture teatment at Wajo regency, South Sulawesi province. A research method by purposive random sampling of 703 samples of elderly people with age equal or above 55 years old by fulfilling a questioner. The result of this study showed that all of 703 samples had tooth loss, 29,26% with 1-10 tooth loss, 28,0% with 11-20 tooth loss, more than 20 teeth (42.1%), and edentulous 0,7%. Only 1 % of the samples used denture. In conclusion, knowledge of community related oral and dental health and the importance of substituting tooth loss with denture is very limited or low.